Identification of family determining residues in Jumonji‐C lysine demethylases: A sequence‐based, family wide classification. Issue 3 (16th February 2016) - Slama, Patrick
ABSTRACT: Histone post‐translational modifications play a critical role in the regulation of gene expression. Methylation of lysines at N‐terminal tails of histones has been shown to be involved in such regulation. While this modification was long considered to be irreversible, two different classes of enzymes capable of carrying out the demethylation of histone lysines were recently identified: the oxidases, such as LSD1, and the oxygenases (JmjC‐containing). Here, a family‐wide analysis of the second of these classes is proposed, with over 300 proteins studied at the sequence level. We show that a correlated evolution analysis yields some position/residue pairs which are critical at comparing JmjC sequences and enables the classification of JmjC domains into five families. A few positions appear more frequently among conditions, such as positions 23 (directly C‐terminal to the second iron ligand), 24, 252 and 253 (directly N‐terminal to a conserved Asn). Implications of family conditions are studied in detail on PHF2, revealing the meaningfulness of the sequence‐derived conditions at the structural level. These results should help obtain insights on the diversity of JmjC‐containing proteins solely by considering some of the amino acids present in their JmjC domain. Proteins 2016; 84:397–407. © 2016 Wiley Periodicals, Inc.